Two Tachykinin-Related Peptides with Antimicrobial Activity Isolated from Triatoma infestans Hemolymph. (July 2020) - Diniz, Laura Cristina Lima; Alves, Flávio Lopes; Miranda, Antonio; Silva Junior, Pedro Ismael da
Antimicrobial peptides and proteins (AMPs) are molecules that can interact with microbial cells and lead to membrane disruption or intracellular molecule interactions and death. Several molecules with antimicrobial effects also present other biological activities. One such protein group representing the duplicity of activities is the tachykinin family. Tachykinins (TKs) form a family of neuropeptides in vertebrates with a consensus C-terminal region (F-X-G-Y-R-NH2). Invertebrate TKs and TK-related peptides (TKRPs) are subfamilies found in invertebrates that present high homology with TKs and have similar biological effects. Several of these molecules have already been described but reports of TKRP in Hemiptera species are limited. By analyzing the Triatoma infestans hemolymph by reversed-phase high-performance liquid chromatography, biological assays, and mass spectrometry, two antimicrobial molecules were isolated and identified as TKRPs, which we named as TRP1-TINF and TRP2-TINF (tachykinin-related peptides I and II from T. infestans ). TRP1-TINF is a random secondary structure peptide with 9 amino acid residues. It is susceptible to aminopeptidases degradation and is active mainly against Micrococcus luteus (32 μM). TRP2-TINF is a 10-amino acid peptide with a 310 helix secondary structure and is susceptible to carboxypeptidases degradation. It has major antimicrobial activity against both Pseudomonas aeruginosa and Escherichia coli (45 μM). Neither molecule is toxic to human erythrocytes and both present minor toxicity toward Vero cells at a concentration of 1000 μM. As the first description of TKRPs with antimicrobial activity in T. infestans, this work contributes to the wider comprehension of the insects' physiology and describes pharmacological relevant molecules.